Pendidikan Filosofis untuk Kesadaran Ekologis : Menumbuhkan Kesadaran Moral terhadap Lingkungan di Kalangan Siswa Sekolah Menengah Kejuruan Perpajakan Riau - Hardianti, Sri; Firdaus, M; Saputra, Decky; Sumianto; Febria, Dessyka; Iqbal Firmananda, Fahmi; Zulia Jati, Putri; Indah Permatha Sari, Vigi (Journal of Social and Community Service, 2024)
This community service aims to increase environmental awareness and the formation of moral character of students at SMK Perpajakan Riau with an approach based on educational philosophy and environmental ethics. This activity involves an understanding of global and local environmental issues, as well as an introduction to environmental ethics that connects moral values ​​with responsibility towards nature. The methods used include counseling, group discussions, and environmental projects that involve students in concrete actions, such as planting trees and reducing plastic waste. Evaluation was carried out through questionnaires before and after the activity to measure changes in students' knowledge, attitudes, and commitment to the environment. The results showed a significant increase in students' understanding of environmental issues and concrete actions that can be taken to maintain sustainability. Although moral awareness of the environment increased, the greatest impact was seen in changes in students' knowledge and real actions. With this approach, it is hoped that students will not only have strong environmental knowledge, but also a character that cares and is responsible for nature. This activity reflects the integration between the theory of educational philosophy and the practice of sustainability in education.